2012
DOI: 10.1007/s11947-012-0957-8
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Dehydration of Nectarines: Influence of the Operating Conditions and Determination of the Effective Diffusion Coefficients

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided ackn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
2
26
0
2
Order By: Relevance
“…But when the image analysis was used, the deviations were not significant; hence, it is concluded that when the appearance is not homogenous, it is advisable to use the image analysis to evaluate color (Rodríguez et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…But when the image analysis was used, the deviations were not significant; hence, it is concluded that when the appearance is not homogenous, it is advisable to use the image analysis to evaluate color (Rodríguez et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Rodríguez et al . ). Finally, the color stability during storage leads to the conclusion that drying by combined methods allows preserving plums without important modifications in their appearance.…”
Section: Resultsmentioning
confidence: 97%
“…Rodríguez et al (2013) não observaram influência significativa da temperatura sobre Desenvolvimento e avaliação sensorial de goiaba-passa desidratada osmoticamente Castro, D. S. et al a perda de água em seus estudos sobre a desidratação osmótica de nectarinas.…”
Section: Resultsunclassified
“…Over the past few years, studies on the dehydration of stone fruits such as plums [1,2], cherries [3,4], peaches [5], apricots [6,7] and nectarines [8][9][10] have been performed owing to the nutritional properties of these fruits and in the interest of obtaining a long shelf-life with the best possible quality. Fruits such as nectarines have a high moisture content and are susceptible to physical and chemical changes that cause their decomposition.…”
Section: Introductionmentioning
confidence: 99%